Spiritualitas Manusia dalam Menata “Jalan Pulang” - Betty Tresnawaty (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2015)
There is so many ways to convey the message or information. Likewise in conveying religious messages to build awareness of man in enhancing the spiritual and morality. Morality is a sense of loyalty to the duties and responsibilities. Humans as moral beings can not be understood, unless it first recognizes the reality of the Lord of Hosts, source of Personality. When people fail to distinguish the objectives of his trip, he met his own work at the level of the presence of the animal. He had failed to seize the opportunity advantages over the intelligence material, moral discrimination, and spiritual wisdom that are integral part of the gift of its consmic-mind as a man who has a personality.